CO2 capture and separation over N2 and CH4 in nanoporous MFM-300(In, Al, Ga, and In-3N): Insight from GCMC simulations. (December 2018) - Wu, Zhonghua; Wei, Shuxian; Wang, Maohuai; Zhou, Sainan; Wang, Jiahui; Wang, Zhaojie; Guo, Wenyue; Lu, Xiaoqing
Graphical abstract: Systematic analyses on CO2 adsorption uptake, selectivity, adsorption heat, and interactions of CO2 –framework and CO2 -CO2 illustrated that MFM-300(In, Al, Ga, and In-3N) can create a favorable environment for high-efficiency CO2 capture and separation over N2 and CH4 in a low-concentration environment. Highlights: MFM-300 create a favorable environment for CO2 capture and separation over N2 /CH4 . MFM-300(In) is high-efficiency for CO2 adsorption in low-concentration environment. Large adsorption heat difference results in large selectivity of CO2 over N2 /CH4 . The CO2 –framework interaction has major contribution to the total interactions. Abstract: CO2 capture and separation over N2 and CH4 in MFM-300(In, Al, Ga, and In-3N) were investigated by grand canonical Monte Carlo (GCMC) simulations. Results showed that four nanoporous MFM-300 materials could construct a feasible CO2 adsorption environment with suitable surface area, pore size, and porosity. MFM-300(In) exhibited an excellent CO2 adsorption uptake of 8.0 mmol g −1 at 298 K and 1.0 bar. At the low pressures, the CO2 adsorption uptake was in the sequence of MFM-300(In) > MFM-300(Al) > MFM-300(Ga) > MFM-300(In-3N) with the sharp "ramp-up" type selectivity. At the equilibrium state, the selectivities of CO2 /N2 and CO2 /CH4 in MFM-300(In) reached up to 300 and 120, respectively. The adsorption heat and interactions of CO2 -CO2 and CO2 –framework were then analyzed to elucidate the adsorption ability, adsorption uptake, selectivity, and interaction mode of three gases in four MFM-300 materials. This work highlighted the potential nanoporous materials of MFM-300(In, Al, Ga, and In-3N) for CO2 capture and separation over N2 and CH4 .